Description of Energy, Protein, Iron and Folic Acid Intake in Pregnant Women Protein Energy Malnutrition at Sobo Health Center Banyuwangi City - Dhea Martadilla; Annas Buanasita; Nuning Marina Pengge; Mujayanto; Fahmi Hafid; Ang Yeow Nyin (Politeknik Kesehatan Kemenkes Surabaya, 2024)
Protein Energy Malnutrition (PEM) is one of the prevailing nutritional issues in Indonesia. Dietary intake is a crucial factor related to malnutrition in pregnant women, with the common impact being Low Birth Weight (LBW) of babies. This research examines the intake of energy, protein, iron, and folate among pregnant women with PEM in the working area of Sobo Health Center, Banyuwangi City. The study is descriptive in nature and involves 15 pregnant women with PEM from the Sobo Health Center area as respondents. Data collection involved filling out personal sheets, measuring upper arm circumference using a LiLA tape, and conducting 2x24-hour food recall interviews. Descriptive analysis was performed using frequency distribution tables generated by the SPSS program. The research findings indicate that among pregnant women with severe energy deficiency PEM, all 15 individuals (100%) had severe energy deficit, 7 individuals (46.7%) had severe protein deficit, and all 15 individuals (100%) had insufficient dietary intake to meet their nutritional needs during pregnancy.